(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current knowledge and practice on nutrition of out-patients with type 2 diabetes at Nghe An Hospital of Endocrinology in 2024. Method: A cross-sectional descriptive study was conducted on 95 out-patients with type 2 diabetes at the Nghe An Hospital of Endocrinology during the period from June to October 2024. Results: The average age is 66.3 ± 8.7 years; 67.4% are female; 57.9% live in rural areas, and 40% have a high school education, with 44.1% being farmers and 34.5% having a family history of diabetes. Out of 95 individuals, 45 have diabetes complications or comorbidities, with 46.1% having hypertension. The knowledge rate regarding dietary habits among type 2 diabetes patients is 70.3%; the average knowledge score is 8.1 ± 3.2. The percentage of patients with adequate practice regarding diabetes nutrition was 61.6%. The mean score of practice was 13.0 ± 2.7. Conclusion: The knowledge and practice regarding the dietary regimen of outpatient type 2 diabetes patients at the Nghe An Hospital of Endocrinology is still low. It is necessary to enhance health education about nutrition for these patients.